“E-UKGM” Model as an Effort to the Recording and Reporting Quality of Community Dental and Oral Health Efforts (UKGM) in Community Health Centers - Wulandari, Ayu; Supriyana, Supriyana; Sunarjo, Lanny (Universitas Padjadjaran, 2025)
UKGM is a dental health service activity carried out by the community through guidance from the community health center. The obstacle to implementing UKGM is that the recording and reporting that has been implemented at community health centers is still manual. In the Bulukumba Regency area recording and reporting of UKGM activities is still carried out manually, UKGM activity reports are combined with other health reports, and there is no ongoing action data from the results of examinations on UKGM activities. Efforts are needed to increase the recording and reporting of UKGM activities at health centers based on information systems. Purpose this activity proving that the E-UKGM model is effective as an effort to increase UKGM recording and reporting in community health centers. Method research and development with Pre-eksperiment one Group Pretest-Posttest Design. The research sample was 20 TGM who worked in community health centers who were given the E-UKGM model. Data collection techniques are interviews and questionnaires. Data were processed using non-parameteric tests. The results that expert validation test against the E-UKGM model obtained an average of 82% in the very feasible category andr>0.726. The recording and reporting mechanism, and the quality of data and information increased after being given the “E-UKGM” model compared to the previous p-value of 0,000 (p<0,05). The onclusion is the implementation of the E-UKGM model is effective in improving the quality of UKGM recording and reporting in community health centers.Keywords: Recording and reporting, UKGM, information systems.